2021
DOI: 10.3390/ijerph18105159
|View full text |Cite
|
Sign up to set email alerts
|

Are Healthcare Workers at an Increased Risk for Obstructive Respiratory Diseases Due to Cleaning and Disinfection Agents? A Systematic Review and Meta-Analysis

Abstract: Several reviews have reported an increased risk of obstructive respiratory diseases in workers exposed to cleaning or disinfection agents, but they have focused mainly on professional cleaners. Cleaning and disinfecting are frequently performed activities by healthcare workers. We conducted a systematic review with meta-analysis to quantify the risk of obstructive respiratory diseases in healthcare workers exposed to cleaning and disinfection agents. We searched the Medline and Embase databases until 4 Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In conclusion, this review found a higher risk of asthma among healthcare workers exposed to cleaning or disinfecting tasks or agents. These findings are consistent with the results of previously conducted systematic reviews 8,43 . Compared with this review, both previous reviews determined a greater increase in asthma risk associated with cleaning or disinfecting tasks 8,43 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, this review found a higher risk of asthma among healthcare workers exposed to cleaning or disinfecting tasks or agents. These findings are consistent with the results of previously conducted systematic reviews 8,43 . Compared with this review, both previous reviews determined a greater increase in asthma risk associated with cleaning or disinfecting tasks 8,43 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with the results of previously conducted systematic reviews. 8,43 Compared with this review, both previous reviews determined a greater increase in asthma risk associated with cleaning or disinfecting tasks. 8,43 The limitations found in this review may contribute to a potential underestimation of the risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological research on health effects from cleaning and disinfection agents generally focus on cleaning and nursing occupations ( Quirce and Barranco, 2010 ; Van den Borre and Deboosere, 2018 ; Carder et al , 2019 ; De Matteis et al , 2020 ; Dumas and Le Moual, 2020 ; Archangelidi et al , 2021 ; Romero Starke et al , 2021 ). To some extent the SWEA data confirm expected patterns regarding in which sectors and occupations diseases and injuries occur, however, the full range of sectors and occupations covered by the ISA data show the wide-spread use of this product group.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies point towards links between use of cleaning agents and lung disease ( Quirce and Barranco, 2010 ; Van den Borre and Deboosere, 2018 ; Carder et al , 2019 ; De Matteis et al , 2020 ; Dumas and Le Moual, 2020 ; Archangelidi et al , 2021 ; Romero Starke et al , 2021 ). A Belgian registry study found increased mortality in respiratory and cardiovascular diseases among cleaners ( Van den Borre and Deboosere, 2018 ).…”
Section: Introductionmentioning
confidence: 99%